Ta'tsir istikhdam namudzaj al ta'lim al ta'awuniy bi al 'asha al nathiqah (talking stick) li tarqiyati maharah al kalam li ta'allumi al lughah al 'arabiyah lada al thullab fi al madrasah al mutawassithah al hukumiyah al wahidah Hiliran Gumanti - Nur Aini; R. Taufiqurrochman; Nur Ila Ifawati (Tarling, 2025)
Speaking in a foreign language is a big challenge for many students, especially when the learning methods used are less interesting and interactive. This study aims to analyze the effect of the Talking Stick strategy on improving students' maharah. The research approach used is Quantitative Research. The type of research is quasi-experiment with pretest-posttest control group design. The subjects of this study were students of class IX 1 as the control class and class IX 2 as the experimental class in a junior high school. The research instruments included oral tests to measure students' maharah kalam. The data obtained were analyzed using statistical tests to determine the difference in learning outcomes between the control class and the experimental class. The results showed that there was a significant difference between the two classes. With the comparison value of the mean results during the pretest and posttest, namely the pretest in the experimental class 63.5 with the criteria of Dhaif and posttest 76.0 with Maqbul criteria, while the pretest in the control class 61.67 with the criteria of Dhaif and posttest 66.67 with Dhaif criteria as well. Students who learned with the Talking Stick strategy experienced a greater improvement in speaking ability compared to students in the control class.  Thus, Talking Stick strategy can be used as an effective alternative in Arabic language learning to improve students' speaking skills and learning motivation.